Effect of steam explosion pretreatment on polysaccharide isolated from Poria cocos: Structure and immunostimulatory activity. Issue 10 (27th July 2022) - Liang, Jiehua; Zhao, Minhao; Xie, Siwei; Peng, Dong; An, Miaoqing; Chen, Yang; Li, Pan; Du, Bing
Abstract: This study aimed to examine the effects of steam explosion (SE) pretreatment on the structural characteristics and immunostimulatory activity of polysaccharide from Poria cocos . Results showed that the average molecular weights of native polysaccharide (PCP) and SE‐pretreated polysaccharide (SEPCP) were 18.67 and 6.52 kDa, respectively. PCP and SEPCP shared the same profiles of monosaccharides (mannose, glucose, galactose, and fucose) in different composition ratios, that is, PCP in a molar percentage of 13.5:33:40.3:13.2 and SEPCP in a molar percentage of 2.1:90.3:5.8:1.8. The surface structure of PCP showed smooth and densely spherical particles, whereas SEPCP had a rough surface and porous honeycomb structure. The main linkage types of PCP comprised 1, 6‐α‐d ‐Gal p, 1, 2, 6‐α‐d ‐Glc p, and T‐α‐d ‐Man p, whereas SEPCP primarily contained 1, 3‐β‐d ‐Glc p backbone and T‐β‐d ‐Glc p branches. Compared with PCP, we further revealed that SEPCP had a better immune enhancement on the phagocytic ability, NO production, and the secretion levels of TNF‐α and IL‐6 in RAW 264.7 cells. Collectively, our observations supported that SE pretreatment could help to change the structure and improve the immunostimulatory activity of polysaccharide from P. cocos . Practical applications: SE technology is extensively used to extract bioactive components with improved yields owing to this technology's benefits of low energy consumption and high efficiency. SE pretreatment was found to contribute to the destruction of cell‐wall structure, which could help to enhance the extraction yields of P. cocos polysaccharide (PCP). Meanwhile, SE pretreatment also could change the structural features and improve the immunostimulatory activity of PCP. This study revealed that more bioactive PCP with strengthened immunoregulatory effect was obtained pretreated by SE. This study was able to provide the effective information on the application of steam explosion technology to promote the further development and utilization of PCP in the pharmaceutical and functional food fields. Abstract : The steam explosion pretreatment changed the structural properties of Poria cocos polysaccharide and exhibited a better immune‐enhancing effect by promoting the secretion levels of NO, TNF‐α, and IL‐6 in RAW 264.7 cells. The steam explosion pretreatment is an effective method for obtaining bioactive P. cocos polysaccharide with strengthened immunoregulatory activity.